College Academic Stress: Differences along Gender Lines - Calaguas, Glenn M. (Journal of Social and Development Sciences, 2011)
This study examined the perception of academic stress among college students in a state college in the Philippines highlighting gender differences. In order to achieve the purpose of the study, an indigenous survey instrument was developed. A total of 1,210 college students chosen through systematic random sampling responded to the survey instrument. To determine gender differences among the respondents, independent samples t-test was used via SPSS version 15.0. Statistical analyses showed that male and female respondents differed significantly in their perceptions of subject, teacher, schedule, classroom, and expectation-related stressors but did not significantly differ in their perceptions of enrolment and admission, classmate, and financial- related stressors. Generally, no significant difference was found between male and female respondents in their perception of academic stressors, however using the mean scores as basis, female respondents scored higher compared to male respondents.